Impact of health care financing reforms on the management of malaria in Ghana - Biritwum, R.B. (East African Medical Journal, 2001)
Objective: To determine the impact of the introduction of the 'cash and carry' system on how health care providers manage malaria cases in Ghana Design: A cross sectional study of treatment patterns of cases of malaria. Setting: Health services in Ghana changed significantly in 1992, from being virtually free to a 'cash and carry' system in which all patients attending government health services had to pay in full for drugs and services. Staff of private companies and parastatal organisations continue to enjoy free health services at other clinics and hospitals. Subjects: Prescriptions for 9539 cases diagnosed as having malaria at the out-patient departments (OPD) of eight health facilities four in the 'cash and carry' scheme and four outside this scheme were reviewed. Results: The mean (SD) number of drugs prescribed per case of malaria was higher for the 'cash and carry' group than for the 'free for service' group; 4.5±1.3 versus 3.8±1.3 (p value <.001). Injection chloroquine was used more frequently in the 'cash and carry' group than in the 'free service' group 56.4% and 28.6% respectively (p value < .001). Second-line antimalarial drugs were however, more often used in the 'free service' group 13.5% versus 7.3% (p value <.001). About 30% of the 'cash and carry' group received antibiotics, compared with 15.5% of the 'Free Service' group. Logistic regression analysis showed that the modality of payment for services contributed significantly to whether a case of malaria was managed with more than three drugs, or received injection chloroquine or antibiotics or a non-steroidal anti-inflammatory drug. Conclusion: Evidence in this study suggests that health care providers tend to pay more attention in treating the symptoms of malaria in cases in which patients pay for service. This leads to unnecessarily high costs of care for the individual and the health system.
Keywords: Impact of health care; Health care; Health care financing reforms; Malaria; Ghana